2017
DOI: 10.1021/acs.est.7b02480
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Antibiotic Florfenicol by Sulfide-Modified Nanoscale Zero-Valent Iron

Abstract: Florfenicol (FF, CHClFNOS), an emerging halogenated organic contaminant of concern was effectively degraded in water by sulfidized nanoscale zerovalent iron (S-nZVI). Sulfidized nZVI (62.5 m g) that was prepared using a one-step method resulted in small Fe/Fe-sulfide particles that were more stable against aggregation than unsulfidized nZVI (10.2 m g). No obvious removal of FF was observed by unsulfidized nZVI. S-nZVI degraded FF, having a surface area normalized reaction rate constant of 3.1 × 10 L m min. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(102 citation statements)
references
References 67 publications
4
96
0
2
Order By: Relevance
“…Recently, it was shown by us and others that the sulfidation of NZVI lowers its reactivity with water and other non‐target hydrophilic contaminants (e.g., NO 3 − ), while increasing its reactivity with target contaminants like chlorinated solvents and antibiotics. [ 25–31 ] Several mechanisms have been hypothesized for the enhanced reactivity and selectivity of sulfidized nanoscale zerovalent iron (SNZVI) compared to NZVI. First, SNZVI is more hydrophobic than NZVI, resulting in lower interaction with water and charged solutes, and greater interaction with hydrophobic contaminants.…”
Section: Figurementioning
confidence: 99%
“…Recently, it was shown by us and others that the sulfidation of NZVI lowers its reactivity with water and other non‐target hydrophilic contaminants (e.g., NO 3 − ), while increasing its reactivity with target contaminants like chlorinated solvents and antibiotics. [ 25–31 ] Several mechanisms have been hypothesized for the enhanced reactivity and selectivity of sulfidized nanoscale zerovalent iron (SNZVI) compared to NZVI. First, SNZVI is more hydrophobic than NZVI, resulting in lower interaction with water and charged solutes, and greater interaction with hydrophobic contaminants.…”
Section: Figurementioning
confidence: 99%
“…The diffraction peak of S-nZVI@MC is sharper, indicating that sulfidation can enhance the crystallinity of nZVI. There is no peak of sulfur species (FeS or FeS2) on the XRD pattern of S-nZVI@MC, which may be due to the low sulfur content or poor crystallinity of sulfur species [25]. After 3 h of reaction with TCP, the peak intensity of S-nZVI@MC has no obvious decrease.…”
Section: Characterizationmentioning
confidence: 96%
“…However, a weaker diffraction peak of Fe2O3 was observed, indicating that only part of the nZVI reacted with TCP. In addition, the reaction between such non-target reactants as H2O and nZVI should be effectively inhibited, which is attributed to the protection effect of FeS [25]. In order to further verify the formation of Fe and S before and after the reaction with TCP, XPS spectra were further analyzed.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more recently, Cao et al have shown that NZVI with a sulfur based shell, (S-NZVI) is able to degrade florfenicol (FF), which is considered a target molecule for ABs. The removal efficiencies were good in groundwater, river water, seawater, and wastewater [63]. In their interesting system, the shell is formed by Fe x S y , which has a higher affinity with the hydrophobic part -Cl and -F group on FF compared to the more hydrophilic iron oxides-hydroxides and also facilities electron transfer due to a lower bandgap than Fe x O y .…”
Section: Reaction With Nanoscale Zero Valent Ironmentioning
confidence: 99%